2015
DOI: 10.1111/ics.12244
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physically applied alpha hydroxyl acids on the skin pore and comedone

Abstract: 4% AHA solution combined with a physical effect had rapidly improving effects on whiteheads and blackheads synergistically. Combined physical therapy may have more impact on pore size and seborrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…In addition, we confirmed that 4% AHA solution combined with physical dermabrasion synergistically resulted in rapid improvement in whiteheads and blackheads in human skin [4].…”
Section: Introductionsupporting
confidence: 68%
“…In addition, we confirmed that 4% AHA solution combined with physical dermabrasion synergistically resulted in rapid improvement in whiteheads and blackheads in human skin [4].…”
Section: Introductionsupporting
confidence: 68%
“…It is considered useful in reducing the size of follicular ostia and in removing comedones. 101 A topical combination containing 10.4% L-lactic acid, 2% salicylic acid and alpha-hydroxy acid/retinoate conjugate (ethyl lactyl retinoate) was used in the topical treatment of females of ages 20 to 58. After 4 weeks, improvement was achieved, which remained continuous and cumulative in the eighth week.…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…Exfoliating products containing the acids show antibacterial, keratolytic, and antioxidant effects, which make them popular in anti-aging treatments (National Toxicology Program, 2007; Sharad, 2013; Sharquie et al, 2014). Exfoliating cosmetic products are commonly used for the treatment of acne, with a concentration of AHAs typically ranging from 5 to 10%, but can cause effective sebum removal with a lesser AHA concentration (4%) when physical pressure is applied (Kim et al, 2015). However, published studies confirm that topically applied AHAs may increase skin sensitivity to the sun, especially to UVB-irradiation (Fiume, 2017; Tang and Yang, 2018).…”
Section: Introductionmentioning
confidence: 99%